Hafnium dioxide nanomaterial, positive electrode sheet and sodium telluride battery

By using a method of cross-connecting hafnium dioxide nanomaterials that form cluster structures and a method of loading tellurium element by dissolving and sedimentation of potassium hydroxide, the shuttle effect, volume expansion and ohmic polarization problems of sodium tellurium batteries during charging and discharging are solved, and the cycle stability and conductivity of the batteries are improved.

CN116605905BActive Publication Date: 2025-04-15NANTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310636536.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2025-04-15
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

There are problems of shuttle effect, volume expansion and ohmic polarization during the charge and discharge process of sodium tellurium batteries, resulting in a decrease in energy density and cyclic stability, and it is difficult for the prior art to effectively solve these problems.

Method used

Hafnium dioxide nanomaterial with a clustered structure composed of cross-connection is used as the matrix layer material of the positive electrode sheet, and the tellurium element is loaded by the potassium hydroxide dissolution and sedimentation method to regulate the size and thickness of the hafnium dioxide nanosheets to build a porous structure, and improve the structural stability and cycling performance of the battery.

Benefits of technology

By regulating the structure of hafnium dioxide nanomaterials, it can effectively alleviate the problems of shuttle effect, volume expansion and ohmic polarization, improve the cyclic stability and conductivity of sodium tellurium batteries, and extend the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116605905B_ABST
    Figure CN116605905B_ABST
Patent Text Reader

Abstract

The invention discloses a hafnium dioxide nanomaterial, a positive electrode sheet and a sodium tellurium battery, belonging to the technical field of batteries. The hafnium dioxide nanomaterial is composed of hafnium dioxide nanosheets cross-connected to form a cluster structure; the crystal structure of the hafnium dioxide nanosheet is an orthorhombic system, the shape of the hafnium dioxide nanosheet is circular, the sheet diameter is 200-400nm, and the thickness is 5-10nm. The hafnium dioxide nanomaterial is used for the positive electrode sheet, and the positive electrode sheet is used for the sodium tellurium battery. The size and thickness of the hafnium dioxide nanosheet can effectively improve the performance of the sodium tellurium battery, and the potassium hydroxide dissolution sedimentation method is used to further improve the performance and stability of the sodium tellurium battery, and the cycle stability of the battery is improved by a suitable compaction density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a hafnium dioxide nanomaterial, a positive electrode sheet and a sodium tellurium battery. Background Art

[0002] Sodium telluride battery is a type of secondary battery that uses single tellurium as the positive electrode active material. It has an ultra-high theoretical energy density of up to 1285Wh / kg, far exceeding traditional lithium-ion batteries. Sodium telluride batteries use metallic sodium as the negative electrode of the battery, which can effectively avoid the adverse effects of lithium dendrites on battery performance. In addition, sodium telluride battery electrode materials also have the advantages of low cost, environmental friendliness and recyclability, so they have the potential for large-scale application in the fields of portable electronic devices and new energy vehicles.

[0003] However, sodium telluride batteries are still in the laboratory research stage and face many problems in practical application: (1) "Shuttle effect": the discharge product of the positive electrode reaction of sodium telluride batteries is polytelluride, which is very easy to separate from the positive electrode and dissolve into the organic electrolyte. Under the influence of concentration polarization, long and short chain reactions occur and finally Na 2 Te and Na 2 Te 2 The surface of the Na negative electrode is deposited in the form of , which causes an irreversible decrease in the battery energy density and cycle stability; (2) "Volume expansion": During the battery charging and discharging process, the redox reaction products of the active substances on the positive electrode (Na 2 Te、Na 2 Te 2 ) density changes will cause the expansion and contraction of the electrode, resulting in volume expansion and failure of the battery; (3) "Ohmic polarization": the discharge product of single-element tellurium is a poor conductor, which leads to an increase in the internal resistance of the battery. The resulting ohmic polarization will cause the operating temperature of the sodium telluride battery to be too high, causing safety problems.

[0004] The existing technical solutions usually reduce the resistivity of the positive electrode, improve the stability of the electrode and curb the volume change of the electrode by introducing a lighter conductive matrix layer material into the tellurium positive electrode. This technical solution can effectively solve the above technical problems, but it also puts forward strict requirements on the physical and chemical properties of the matrix layer material. First of all, the density of the matrix layer material must be low enough. The matrix layer material that occupies too high a proportion of the positive electrode mass will lead to a decrease in the energy density of the positive electrode of the sodium tellurium battery, which directly affects the battery's capacity; in addition, the conductive matrix layer material needs to have a higher electronic conductivity and ionic conductivity to reduce the internal resistance of the sodium tellurium battery positive electrode, curb the ohmic polarization problem of the sodium tellurium battery, and maintain the stability and safety of the battery operation. Therefore, the academic community has recently made preliminary attempts to use carbon-based lightweight conductive materials as carriers of tellurium positive electrodes in sodium-tellurium batteries, mainly including: carbon fiber (Huang XL, Dou SX, Wang Z M. Fibrous cathode materials for advanced sodium-chalcogen batteries[J]. Energy Storage Materials, 2022, 45: 265-280.), carbon nanorods (Wang H, Tong Z, Yang R, Huang Z, Shen D, Jiao T, Cui X, Zhang W, Jiang Y, Lee CS. Electrochemically Stable Sodium Metal-Tellurium / Carbon Nanorods Batteries[J]. Advanced Energy Materials, 2019, 9(48): 1903046.), carbon sponge (Li Y, Zhan Y, Xu Q, Hu L, Shen B, Liu H, Dai C, Bao S, Xu M. Nitrogen-Doped Carbon as a Host for Telluriumfor High-Rate Li-Te and Na-Te Batteries[J].Chemsuschem,2019,12(6):1196-1202.) and ordered mesoporous carbon (Koketsu T,Wu C,Huang Y,Strasser PA high-performance Te@CMK-3 composite negative electrode for Na rechargeable batteries[J].Journal of Applied Electrochemistry,2018,48(11):1265-1271.) and other technical solutions.These methods have initially improved the ohmic polarization problem caused by the poor conductivity of pure tellurium positive electrode by using carbon-based materials with high electronic conductivity, and generally meet the requirement that the mass proportion of carbon-based materials in the positive electrode material system is less than 20%, which can effectively maintain a high battery energy density level. However, since there is no strong adsorption capacity between the intermediate products (multiple tellurides) generated by the positive electrode materials of sodium tellurium batteries during operation and the carbon matrix layer, the influence of the "shuttle effect" on the performance attenuation of sodium tellurium batteries cannot be effectively solved, and the combination of carbon-based materials and tellurium in the electrode materials is in the form of intermolecular forces. Too low adsorption energy can easily cause the electrode materials to dissociate and destroy during the electrochemical reaction, resulting in the average battery attenuation per charge and discharge cycle generally being higher than 0.1%. Therefore, it is necessary to select a new sodium tellurium battery positive electrode matrix layer material with high adsorption energy for multiple tellurides to solve the problems of the above-mentioned carbon matrix layer materials.

[0005] Recently, the application of transition metal oxides (TMOs) in the matrix layer materials of sodium telluride batteries has gradually attracted attention. They also have high conductivity, chemical stability and good catalytic activity, which can accelerate the reaction kinetics of sodium telluride batteries and improve the cycle life of batteries. Transition metal oxides can have both good adsorption capacity and thermodynamic stability for polytellurides, and have excellent potential to replace carbon materials. Patent CN105185958A discloses that the transition metal oxide materials suitable for the positive electrode matrix layer of sodium telluride batteries are titanium dioxide, tin oxide, molybdenum oxide, etc. However, the above technical solutions have the following problems: (1) It cannot solve the problem that the chemical reaction between transition metal oxides and sodium ions may cause structural destruction and capacity attenuation of the matrix layer material; (2) Transition metal oxides have a large band gap, resulting in poor ionic conductivity and electronic conductivity, and the influence of ohmic polarization still exists; (3) The microscopic morphology of metal oxides is mainly blocks and spheres, with a small specific surface area, making it difficult to load a high mass ratio of tellurium, and the adsorption capacity for polytellurides is limited; (4) Transition metal oxide materials that have not undergone morphology control have a small porosity and cannot effectively resist the influence of volume effect. At present, the technology for controlling material morphology is difficult and costly.

[0006] Although hafnium dioxide nanomaterials have a strong adsorption capacity for the multi-tellurides grown during the positive electrode reaction of sodium telluride batteries due to their clustered shape, the structure of low-dimensional hafnium dioxide nanosheets is not stable enough. During long-term cyclic charge and discharge, the stress in the battery will cause the layered structure of the hafnium dioxide nanosheets to collapse or fail, thereby affecting the stability of the battery. In order to effectively reduce the internal resistance, it is usually necessary to apply a large compaction stress to the matrix layer material, so that the porosity and specific surface area of ​​the hafnium dioxide nanomaterial are low, and the electrolyte in the battery cannot fully penetrate and fill the interior of the hafnium dioxide nanomaterial, resulting in shuttle effect, volume expansion and ohmic polarization problems. The surface of the hafnium dioxide nanomaterial is loaded with tellurium as the active material of the battery. Uneven distribution or low filling degree leads to reduced battery capacity. The uneven distribution of tellurium will lead to inconsistent reactions during the battery charge and discharge process, affecting the battery cycle stability and capacity performance. Summary of the invention

[0007] Purpose of the invention: The first purpose of the present invention is to propose a hafnium dioxide nanomaterial; the second purpose is to provide a method for preparing the hafnium dioxide nanomaterial; the third purpose is to provide a positive electrode sheet of the hafnium dioxide nanomaterial; the fourth purpose is to provide a method for preparing the positive electrode sheet; the fifth purpose is to provide a sodium telluride battery.

[0008] To achieve the above purpose, the present invention adopts the following technical scheme: a hafnium dioxide nanomaterial, wherein the hafnium dioxide nanomaterial is composed of cross-connected hafnium dioxide nanosheets to form a cluster structure; the crystal structure of the hafnium dioxide nanosheet is an orthorhombic crystal system, and the shape of the hafnium dioxide nanosheet is round, the sheet diameter is 200 to 400 nm, and the thickness is 5 to 10 nm.

[0009] The preparation method of the above-mentioned hafnium dioxide nanomaterial comprises the following steps: (I) precursor preparation: taking hafnium telluride tetrahydrate and methyl thioglycolate to mix, fully stirring, adding alkyl alcohol amide and ammonium fluoride to react, filtering and collecting the precipitate after the reaction is completed, and washing to obtain a precursor; (II) low-pressure temperature-controlled oxidation: pre-oxidation heating treatment is performed on the precursor prepared in step (I), and then deep oxidation heating treatment is performed, and then cooling is performed to obtain amorphous hafnium dioxide; (III) vacuum freeze drying: the amorphous hafnium dioxide obtained in step (II) is mixed with ethylene glycol and vacuum pre-frozen, and then dried and heated to obtain amorphous hafnium dioxide nanospheres; (IV) annealing purification: the amorphous hafnium dioxide nanospheres prepared in step (III) are annealed to obtain hafnium dioxide nanomaterials.

[0010] Furthermore, in step (I), the mass ratio of hafnium telluride tetrahydrate, methyl thioglycolate, alkyl alcohol amide and ammonium fluoride is (3-4):(1-1.2):(0.8-1.0):(0.2-0.3).

[0011] In step (I), the stirring condition is to isolate moisture and oxygen for no less than 30 minutes; the reaction condition is to react at 160-165° C. for 4 hours; and the cleaning is to use sufficient acetone for ultrasonic cleaning at a power of 100 watts for 1 hour.

[0012] In step (II), the pre-oxidation heat treatment is to place the precursor prepared in step (I) into a corundum crucible, place it in a tubular vacuum atmosphere annealing furnace, maintain the injection flow rate of high-purity oxygen at 5 ml / min at 0.01 atm, and perform pre-oxidation treatment at 380-400°C for 1 hour; the deep oxidation heat treatment is to slowly increase the injection flow rate of high-purity oxygen to 10 ml / min, and perform deep oxidation treatment at 440-450°C for 2 hours; the cooling rate is controlled at 5°C / min.

[0013] In step (III), the mass ratio of the dried product to ethylene glycol is 1:(2.5-3.5), preferably, the mass ratio of the dried product to ethylene glycol is 1:3; the vacuum pre-freezing treatment is pre-freezing at -50°C for 20 hours; the drying temperature rising step is heating to -35°C at a heating rate of 0.5°C / min, keeping warm for 2 hours, then heating to -10°C at a heating rate of 1°C / min, keeping warm for 4 hours, and finally heating to room temperature at a heating rate of 2.5°C / min, while maintaining the drying environment pressure less than 0.01atm during the heating process.

[0014] In step (IV), the annealing treatment is to place the amorphous hafnium dioxide nanospheres prepared in step (III) into a tubular vacuum atmosphere annealing furnace, the annealing pressure is less than 0.005 atm, and the annealing atmosphere uses high-purity argon or high-purity nitrogen.

[0015] In step (IV), the annealing treatment is carried out at a temperature of 200 to 220° C. and for a time of 3 to 4 hours.

[0016] A positive electrode sheet includes a positive electrode current collector, a matrix layer arranged on one side of the positive electrode current collector, and an active substance loaded on the matrix layer; the positive electrode current collector is aluminum foil, the matrix layer material is the above-mentioned hafnium dioxide nanomaterial, and the active substance is tellurium element.

[0017] The aluminum foil has a thickness of 0.01 to 0.02 mm, a roughness Ra of 0.05 to 0.1 μm, and a roughness Rz of 0.05 to 0.1 μm. Preferably, Ra is 0.05 μm, and Rz is 0.05 μm.

[0018] The microscopic morphology of the tellurium single substance is nano-microspheres with a sphere diameter of 50 to 200 nm.

[0019] A method for preparing the above-mentioned positive electrode sheet comprises the following steps: (1) active material loading: tellurium powder and potassium hydroxide are mixed evenly and then ground, sieved and then added with distilled water, stirred and dissolved to obtain a yellow mixed solution, then the yellow mixed solution is added dropwise to the above-mentioned hafnium dioxide nanomaterial powder to form a light yellow slurry, anhydrous ethanol is added, then the light yellow slurry is wet-ground and dried to obtain tellurium-loaded hafnium dioxide; (2) positive electrode current collector pretreatment: aluminum foil is flattened and then annealed, the treated aluminum foil is immersed in a mixed solution of iodine methanol and phosphoric acid, left to stand, taken out, washed and dried at low temperature to obtain pretreated aluminum foil; (3) positive electrode sheet vacuum coating: the aluminum foil pretreated in step (2) is placed in a vacuum coating machine, the tellurium-loaded hafnium dioxide prepared in step (1) is coated on the surface of the aluminum foil under vacuum heating conditions, and then compacted to obtain a positive electrode sheet.

[0020] In step (1), the mass ratio of tellurium element, potassium hydroxide, distilled water, hafnium dioxide nanomaterial and anhydrous ethanol is (1-1.2):(0.45-0.6):(15-20):(0.25-0.3):(5-6), preferably, the mass ratio is 1:0.5:15:0.25:5.

[0021] In step (1), the wet grinding is to place the light yellow slurry in a vacuum freeze grinder, and the processing conditions of the vacuum freeze grinding are to wet grind and dry for 24 hours at a grinding pressure of 0.02 atm and a freezing temperature of -50°C.

[0022] In step (2), the annealing treatment conditions are heating at 180°C for 4 hours and cooling to room temperature; the drying temperature is 60°C.

[0023] In step (2), the mass fraction ratio of iodine methanol to phosphoric acid in the mixed solution of iodine methanol and phosphoric acid is (1-2):(5-10), preferably, the mass fraction ratio is 1:5.

[0024] In step (3), a co-solvent is added to the tellurium-loaded hafnium dioxide and then coated. The co-solvent is N-methylpyrrolidone, and the mass proportion of the co-solvent in the tellurium-loaded hafnium dioxide is 30% to 40%.

[0025] Preferably, the mass proportion of the co-solvent in the tellurium-supported hafnium dioxide is 35%.

[0026] In step (3), the coating thickness of the tellurium-loaded hafnium dioxide is 50 to 70 μm, preferably, the coating thickness of the tellurium-loaded hafnium dioxide is 70 μm;

[0027] Furthermore, in step (3), the compaction density of the positive electrode sheet is 3.5 to 4 g / cm 3 Preferably, the compaction density of the positive electrode sheet is 3.7 g / cm 3 .

[0028] A method for preparing the above-mentioned positive electrode sheet also includes the following steps: (4) slicing the positive electrode sheet: placing the positive electrode sheet prepared in step (3) on a slicing machine, using molds of different specifications to press the positive electrode sheet and then punching it into a regular and uniform positive electrode sheet; fixing the cut positive electrode sheet with a disc clamp, and using a rolling machine to press and shear the edges of the positive electrode sheet

[0029] In step (4), the punching pressure is 200-300 MPa; preferably, the punching pressure is 300 MPa.

[0030] In step (4), the maximum height of the burrs at the edge of the positive electrode sheet after pressing and shearing is less than 50% of the upper limit of the surface roughness of the positive electrode sheet; the maximum height of the burrs at the edge of the positive electrode sheet is less than 50nm.

[0031] A sodium tellurium battery comprises the above-mentioned positive electrode sheet.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) By regulating the size and thickness of hafnium dioxide nanosheets, the performance of sodium telluride batteries can be effectively improved. While constructing a porous positive electrode sheet, this scheme allows the multi-telluride to be closely combined with the hafnium dioxide nanomaterial in the form of chemical adsorption, providing space for the volume expansion of the battery and alleviating the shuttle effect, volume expansion and ohmic polarization problems. In addition, this regulation also solves the technical contradiction between the mechanical properties of hafnium dioxide nanomaterials and the amount of active material loaded, and improves the structural stability of the positive electrode sheet. Specifically, by controlling the diameter of the hafnium dioxide nanosheet to 200-400nm and the thickness to 5-10nm, the problems of nanosheet agglomeration and collapse can be overcome, and the cycle stability of the battery can be improved.

[0034] (2) Tellurium was loaded on the surface of the matrix layer by potassium hydroxide dissolution precipitation method, and HfO 2Infiltration filling can achieve more uniform tellurium loading and higher filling degree. It can also improve the binding force between hafnium dioxide nanosheets and between aluminum foil and hafnium dioxide nanomaterial matrix layer by regulating the functional groups of hafnium dioxide and aluminum foil surface from oxygen terminal to hydroxyl terminal, and reduce the decay ratio per cycle. However, when using the molten tellurium filling method, the internal pores cannot fully infiltrate tellurium, which will not only lead to a decrease in the active material loading rate, but also lead to an increase in the decay ratio per cycle. Through the potassium hydroxide dissolution sedimentation method, the hafnium dioxide nanomaterial has an appropriate amount of tellurium single substance loading, uniformity and excellent conductivity characteristics, further improving the performance and stability of the sodium tellurium battery.

[0035] (3) The mass surface density of tellurium should satisfy the physical confinement of tellurium in the matrix layer of hafnium dioxide nanomaterials. However, tellurium is a poor conductor. The electrode is pressed with appropriate pressure to give it a reasonable compaction density. Too low a compaction density will not produce performance gain for the electrode, while too high a compaction density will lead to damage to the electrode structure. The compaction density adopted in the present invention not only solves the ohmic polarization problem caused by the low conductivity of hafnium dioxide nanomaterials, but also makes the porosity of the positive electrode sheet conducive to the loading of active substances and the diffusion of carriers on the interface during operation. The specific surface area of ​​the matrix layer after compaction is conducive to the loading of active substances and the sufficient infiltration of the electrolyte. In addition, the appropriate compaction density is used to reduce the distance between the hafnium dioxide nanosheets, increase the binding force between the hafnium dioxide nanosheets, and improve the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the preparation process of hafnium dioxide nanomaterials and positive electrode sheets in Example 1;

[0037] Figure 2 This is a schematic diagram of the structure of the sodium tellurium battery assembled in Example 1;

[0038] Figure 3 The Te / HfO prepared in Example 1 2 XRD pattern of Te / graphene prepared in Comparative Example 1;

[0039] Figure 4 The Te / HfO prepared in Example 1 2 SEM images of

[0040] Figure 5 is the SEM image of Te / graphene prepared in Comparative Example 1;

[0041] Figure 6 This is a graph showing the test data of 100 cycles of sodium telluride battery performance in Example 1;

[0042] Figure 7This is a comparison chart of rate performance test data of sodium telluride battery of Example 1 and Comparative Example 1;

[0043] Figure 8 This is a SEM image of the electrode material microstructure of the sodium telluride battery in Example 1 after 100 cycles of testing. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0045] Example 1

[0046] The hafnium dioxide nanomaterial of this embodiment is composed of cross-linked hafnium dioxide nanosheets to form a cluster structure. The crystal structure of the hafnium dioxide nanosheets is an orthorhombic system. The shape of the hafnium dioxide nanosheets is circular, the diameter of the sheet is 300-400nm, and the thickness is 5-10nm.

[0047] The schematic diagram of the process for preparing the hafnium dioxide nanomaterial of this embodiment is as follows: Figure 1 As shown, it is prepared by the following method:

[0048] All raw materials used in the preparation were of analytical grade and could be used directly. Hafnium telluride tetrahydrate, methyl thioglycolate, alkyl alcohol amide and ammonium fluoride were purchased from Aladdin Chemical Reagent Platform, and ethylene glycol and acetone were purchased from Shanghai Bailingwei Chemical Technology Co., Ltd.

[0049] (I) Preparation of precursor: 4.0 g of hafnium telluride tetrahydrate was mixed with 1.0 g of methyl thioglycolate, and then stirred in an isolated state with no water or oxygen for at least 30 minutes. After the mixture was stirred, 1.0 g of alkyl alcohol amide and 0.25 g of ammonium fluoride were added, and the mixture was reacted at 165° C. for 4 hours. After the reaction was completed, the precipitate was collected by filtration and ultrasonically cleaned with sufficient acetone at a power of 100 watts for 1 hour to obtain a precursor;

[0050] (II) Low-pressure temperature-controlled oxidation: the precursor prepared in step (I) is placed in a corundum crucible, placed in a tubular vacuum atmosphere annealing furnace, and the injection flow rate of high-purity oxygen is maintained at 5 ml / min at 0.01 atm, and pre-oxidation treatment is performed at 400°C for 1 hour; then the injection flow rate of high-purity oxygen is slowly increased to 10 ml / min, and deep oxidation treatment is performed at 450°C for 2 hours; after the heating oxidation is completed, the sample is allowed to cool naturally, and the cooling rate is controlled at 5°C / min to obtain amorphous hafnium dioxide;

[0051] (III) Vacuum freeze drying: 1 g of the obtained amorphous hafnium dioxide was mixed with 3 g of ethylene glycol and subjected to vacuum pre-freezing treatment. The vacuum pre-freezing treatment was performed under the conditions of pre-freezing at -50°C for 20 hours, followed by drying and heating. The drying and heating step was to heat the mixture to -35°C at a heating rate of 0.5°C / min and keep the mixture at that temperature for 2 hours; then heat the mixture to -10°C at a heating rate of 1°C / min and keep the mixture at that temperature for 4 hours, and finally heat the mixture to room temperature at a heating rate of 2.5°C / min. During the heating process, the pressure of the drying environment was maintained at less than 0.01 atm. After the drying was completed, amorphous hafnium dioxide nanospheres were obtained.

[0052] (IV) Annealing purification: The amorphous hafnium dioxide nanospheres prepared in step (III) are placed in a tubular vacuum atmosphere annealing furnace for annealing at 220° C. for 4 hours. The annealing pressure is less than 0.005 atm. High-purity argon is used as the annealing atmosphere to obtain hafnium dioxide nanomaterials.

[0053] The positive electrode sheet of this embodiment includes a positive electrode current collector, a matrix layer disposed on one side of the positive electrode current collector, and an active material loaded on the matrix layer; the positive electrode current collector is aluminum foil, the matrix layer material is the above-mentioned hafnium dioxide nanomaterial, and the active material is tellurium element. From bottom to top, it is composed of aluminum foil, the above-mentioned hafnium dioxide nanomaterial disposed on one side of the aluminum foil, and the tellurium element loaded on the above-mentioned hafnium dioxide nanomaterial. The thickness of the aluminum foil is 0.02 mm, the roughness Ra is 0.05 μm, and the Rz is 0.05 μm; the microscopic morphology of the tellurium element is nano-microspheres with a sphere diameter of 200 nm.

[0054] The schematic diagram of the process for preparing the positive electrode sheet of this embodiment is as follows Figure 1 As shown, it is prepared by the following method:

[0055] All raw materials used in the preparation are of analytical grade and can be used directly. Tellurium powder, potassium hydroxide, anhydrous ethanol, iodine methanol, phosphoric acid, and N-methylpyrrolidone are all purchased from the Aladdin chemical reagent platform.

[0056] (1) Active material loading: 1 g of tellurium powder was mixed with 0.5 g of potassium hydroxide and then ground. After passing through a 200-mesh sieve, 15 ml of distilled water was added and stirred at 80°C to fully dissolve to obtain a yellow mixed solution. The yellow mixed solution was then slowly added dropwise to 0.25 g of hafnium dioxide nanomaterial powder. After a light yellow slurry was formed, 5 g of anhydrous ethanol was added. Finally, the light yellow slurry was placed in a vacuum freeze grinder for vacuum freeze grinding. At a grinding pressure of 0.02 atm and a freezing temperature of -50°C, the mixture was wet-milled and dried for 24 hours to obtain tellurium-loaded hafnium dioxide (Te / HfO 2 );

[0057] (2) Pretreatment of positive electrode current collector: After rolling the aluminum foil flat, place it in a vacuum atmosphere annealing furnace for annealing treatment, heat it at 180°C for 4 hours, and cool it to room temperature; then, prepare a mixed solution of iodine methanol and phosphoric acid with a mass fraction ratio of 1:5; immerse the aluminum foil in 1000 ml of the mixed solution of iodine methanol and phosphoric acid, let it stand for 1 hour, then take it out, rinse it with deionized water and dry it at 60°C to obtain a pretreated aluminum foil;

[0058] (3) Vacuum coating of positive electrode sheet: Place the aluminum foil pretreated in step (2) into a vacuum coating machine, and coat the Te / HfO prepared in step (1) under vacuum heating conditions. 2 After coating on the surface of aluminum foil and compacting, the positive electrode sheet, i.e., Te / HfO 2 Pole piece; in Te / HfO 2 After adding a co-solvent to the coating, the co-solvent is N-methylpyrrolidone, so that the co-solvent is in the Te / HfO 2 The mass percentage of Te / HfO is 35%; 2 The coating thickness is 70μm and the compaction density of the positive electrode is 3.7g / cm 3 ;

[0059] (4) Slicing of positive electrode sheets: The prepared positive electrode sheets are placed on a slicing machine, and a φ15×15 mm punching die is used to punch out regular and uniform circular positive electrode sheets. The cut circular positive electrode sheets are fixed with a disc clamp, and the edges of the positive electrode sheets are pressed and sheared using a rolling machine. The punching pressure is maintained at 300 MPa. The maximum height of the burrs on the edges of the electrode sheets after pressing and shearing is less than 50% of the upper limit of the surface roughness of the electrode sheets, and the maximum height of the burrs on the edges of the positive electrode sheets is less than 50 nm.

[0060] The sodium telluride battery of this embodiment, i.e., Te / HfO 2 The battery includes the above-mentioned positive electrode sheet, and the structure of each main material layer of the sodium telluride battery is as follows Figure 2 As shown, from bottom to top are the current collector, matrix layer and tellurium element of the positive electrode sheet, and the negative electrode and current collector of the negative electrode sheet. The positive electrode sheet and the negative electrode sheet are separated by a separator.

[0061] The sodium telluride battery of this embodiment is prepared by the following method:

[0062] All raw materials used in the preparation were of analytical grade and could be used directly. Sodium foil and copper foil were purchased from Jinan Qiguang Science and Trade Co., Ltd., and Celgard 2500 diaphragm was purchased from Bolitong (Shanghai) Diaphragm Products Co., Ltd.

[0063] The negative electrode sheet adopts a double-layer composite structure of sodium foil and copper foil. A sodium foil with a thickness of 20μm is placed on a copper foil with a thickness of 50μm, vacuum rolled three times in an air-tight environment, and punched into a disc with a diameter of 15mm. The diaphragm adopts the Celgard 2500 model and is cut into a disc with a diameter of 16mm using a punching machine.

[0064] The sodium tellurium battery materials were assembled and packaged using button cells. The battery diaphragm was moistened with 120 μl of electrolyte and then assembled in the order of battery case-gasket-positive electrode sheet-diaphragm-negative electrode sheet-gasket-battery cover. Finally, the assembled battery was placed in a button cell press and packaged using a pressure of 45 MPa.

[0065] Example 2

[0066] The difference from Example 1 is:

[0067] The diameter of the hafnium dioxide nanosheets in this embodiment is 200-300 nm;

[0068] In the method for preparing the hafnium dioxide nanomaterial of this embodiment, the annealing treatment temperature in step (IV) is 200° C. and the time is 3 hours.

[0069] Example 3

[0070] The difference from Example 1 is that the compaction density of the positive electrode sheet is 3.5 g / cm 3 .

[0071] Example 4

[0072] The difference from Example 1 is that the compaction density of the positive electrode sheet is 4.0 g / cm 3 .

[0073] Comparative Example 1

[0074] The positive electrode sheet of this comparative example is composed of an aluminum foil, a graphene nanomaterial disposed on one side of the aluminum foil, and a tellurium element supported on the graphene nanomaterial from bottom to top.

[0075] The positive electrode sheet of this comparative example was prepared by the following method:

[0076] All raw materials used for preparation were of analytical grade and could be used directly. Except for the reagents used in Example 1, graphene nanomaterials were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0077] (1) 1 g of tellurium powder and 0.5 g of potassium hydroxide were mixed and ground, and then passed through a 200-mesh sieve, 15 ml of distilled water was added, and the mixture was stirred and dissolved at 80° C. Then, the yellow mixed solution was slowly added dropwise to 0.25 g of graphene nanomaterial powder, and after a gray-black slurry was formed, 5 g of anhydrous ethanol was added; finally, the gray-black slurry was placed in a vacuum freeze grinder, and wet-milled and dried for 24 hours at a grinding pressure of 0.02 atm and a freezing temperature of -50° C. to obtain Te / graphene;

[0078] (2) After rolling the aluminum foil flat, place it in a vacuum atmosphere annealing furnace, heat it at 180°C for 4 hours, and cool it to room temperature; then, prepare a mixed solution of iodine methanol and phosphoric acid in a mass fraction ratio of 1:5, immerse the aluminum foil in 1000 ml of the mixed solution of iodine methanol and phosphoric acid, let it stand for 1 hour, then take it out, rinse it with deionized water and dry it at 60°C to obtain a pretreated aluminum foil.

[0079] (3) placing the aluminum foil pretreated in step (2) into a vacuum coating machine, coating the Te / graphene prepared in step (1) on the surface of the aluminum foil under vacuum heating conditions, and then compacting the coating to obtain a positive electrode sheet, i.e., a Te / graphene electrode sheet; adding a cosolvent to the Te / graphene and then coating the coating, wherein the cosolvent is N-methylpyrrolidone, and the mass proportion of the cosolvent in the coating is 35%; the coating thickness of the Te / graphene is 70 μm, and the compaction density of the positive electrode sheet is 3.7 g / cm 3 .

[0080] (4) The prepared positive electrode sheet is placed on a slicing machine and punched into a regular and uniform circular positive electrode sheet using a φ15×15mm punching die. The cut circular positive electrode sheet is fixed with a disc clamp, and the edge of the positive electrode sheet is pressed and sheared using a rolling machine, and the punching pressure is maintained at 300Mpa. The maximum height of the burr at the edge of the positive electrode sheet after pressing and shearing is less than 50% of the upper limit of the surface roughness of the electrode sheet, and the maximum height of the burr at the edge of the positive electrode sheet is less than 50nm.

[0081] The sodium tellurium battery of this comparative example, namely the Te / graphene battery, comprises the above-mentioned positive electrode sheet.

[0082] The preparation method of the sodium telluride battery in this comparative example is the same as that in Example 1.

[0083] Comparative Example 2

[0084] Same as Example 1, except that:

[0085] The diameter of the hafnium dioxide nanosheets in this comparative example is 400-500 nm;

[0086] In the preparation method of hafnium dioxide nanomaterials in this comparative example, the annealing temperature in step (IV) is 240° C. and the annealing time is 5 hours.

[0087] Comparative Example 3

[0088] Same as Example 1, except that:

[0089] The thickness of the hafnium dioxide nanosheets in this comparative example is 10 to 15 nm;

[0090] In the preparation method of hafnium dioxide nanomaterial in this comparative example, step (I) is carried out as follows:

[0091] Take 6.0g of hafnium telluride tetrahydrate and mix it with 1.0g of methyl thioglycolate, then isolate it from water and oxygen and stir it for not less than 30 minutes. After completion, add 2.0g of alkyl alcohol amide and 0.3g of ammonium fluoride, and react at 165°C for 4 hours. After the reaction is completed, filter and collect the precipitate and use sufficient acetone to ultrasonically clean it at 100 watts for 1 hour to obtain a precursor.

[0092] Comparative Example 4

[0093] Same as Example 1, except that:

[0094] In the method for preparing the positive electrode sheet of this comparative example, step (1) is performed as follows:

[0095] Take 1g of tellurium powder and 0.25g of hafnium dioxide nanomaterial powder, mix them evenly and grind them. After passing through a 200-mesh sieve, add 20ml of anhydrous ethanol and stir, and dry them at 70°C. Then put the mixed powder into a Pasteur glass tube, heat the two ends of the glass tube at high temperature until they are molten and sealed, and then cool them naturally. Put the sealed glass tube containing the powder into a vacuum tube atmosphere furnace, heat it at 480°C in a high-purity nitrogen atmosphere for 30 minutes, take out the sample after natural cooling and grind it thoroughly to obtain Te / HfO 2 ;

[0096] Comparative Example 5

[0097] Same as Example 1, except that the compaction density of the positive electrode sheet is 3.0 g / cm 3 .

[0098] Comparative Example 6

[0099] Same as Example 1, except that the compaction density of the positive electrode sheet is 4.5 g / cm 3 .

[0100] For the Te / HfO of Example 1 2 The Te / graphene of Comparative Example 1 was subjected to XRD and SEM analysis. The XRD results are shown in Figure 3 The SEM analysis results are shown in Figure 4 and Figure 5 shown.

[0101] The porosity of the positive electrode sheets of Examples 1 to 4 and Comparative Examples 1 to 6, the specific surface area of ​​the matrix layer after compaction, the mass surface density of the tellurium element, the attenuation ratio of the positive electrode sheets per cycle, the conductivity of the positive electrode sheets, and the battery capacity were tested, and the results are shown in Table 1.

[0102] The sodium telluride battery prepared in Example 1 was tested for cycle stability. The results are as follows: Figure 6 shown.

[0103] The sodium telluride batteries of Example 1 and Comparative Example 1 were tested for battery rate performance. The results are as follows: Figure 7 shown.

[0104] Table 1 Comparison of performance of matrix layer, positive electrode sheet and sodium telluride battery in each embodiment and comparative example

[0105]

[0106] As can be seen from Table 1, the porosity of the positive electrode sheets in Examples 1 to 4 is relatively high, ranging from 88.1% to 93.3%, which is conducive to the loading of active materials and the diffusion of carriers on the interface during operation, and the battery performance is good; the specific surface area of ​​the matrix layer after compaction in Examples 1 to 4 is relatively high, ranging from 118 to 134 m 2 / g, and a higher specific surface area is conducive to the loading of active materials and the full infiltration of electrolytes; the attenuation ratio of each cycle of the positive electrode sheets in Examples 1 to 4 is relatively low, between 0.042% and 0.067%, indicating that the structure is stable and the bonding force is good; the conductivity and battery capacity of the positive electrode sheets in Examples 1 to 4 are relatively high, with the conductivity between 0.284 and 0.331 S / m and the capacity between 508.6 and 527.4 mAh / g. Therefore, the positive electrode sheets of Examples 1 to 4 exhibit higher porosity, larger specific surface area, better structural stability, and higher conductivity and battery capacity.

[0107] Figure 4 is the Te / HfO of Example 1 2 From the SEM image, we can see that HfO 2 The nanosheets are interconnected to form a cluster structure, with a diameter of 300-400nm and a thickness of 5-10nm. Te is filled in the pores of the cluster material in the form of nanospheres, and the dispersion between the particles is good.

[0108] from Figure 6 It can be seen that after 100 cycles of testing, the remaining capacity of the battery in Example 1 is still higher than 400 mAh / g, showing excellent battery stability, and the working coulombic efficiency of the sodium telluride battery is stabilized at more than 95%.

[0109] from Figure 4 and Figure 8By comparison, it can be seen that after 100 cycles of the sodium telluride battery in Example 1, the microscopic morphology and structure of the electrode material did not change significantly, the battery performance was stable, and the internal resistance changed little, indicating that the matrix effectively withstood the expansion and contraction of the electrode caused by the electrochemical reaction, solving the volume effect of the sodium telluride battery.

[0110] As can be seen from Table 1, the porosity of the comparative samples is generally low, below 90%. The low porosity is not conducive to the loading of active materials and the diffusion of carriers on the interface during operation, affecting the battery performance; some comparative samples have low specific surface areas, which are not conducive to the loading of active materials and the full infiltration of electrolytes; some comparative samples have high cycle attenuation ratios of positive plates, between 0.045% and 0.109%, and poor structural stability; some comparative samples have low conductivity and capacity, with conductivity between 0.06 and 0.330 S / m and capacity between 450.8 and 506.9 mAh / g. Therefore, these poor indicators are the cause of their poor electrochemical performance and battery performance.

[0111] Compared with Example 1, in Comparative Example 1, due to the use of graphene as the matrix material, the porosity of the positive electrode sheet is reduced. The lower porosity is not conducive to the loading of active materials and the diffusion of carriers on the interface during operation, thus affecting the battery performance. Figure 7 It can be seen that the initial capacity of the sodium telluride battery in Comparative Example 1 is 450.8 mAh g -1 Compared with the above, the initial capacity of the sodium telluride battery of Example 1 increased by 11.6%. This is because the hafnium dioxide nanomaterial has a larger porosity and can load a larger mass density of tellurium active material, thus effectively increasing the initial capacity of the battery. After 100 cycles, the capacity of the sodium telluride battery of Example 1 only decreased by 17.71 mAh·g -1 The average cycle loss rate per cycle is 0.042%, and the capacity of the sodium telluride battery in comparative example 1 is reduced by 38.1 mAh g -1 The average cycle loss rate per cycle is as high as 0.109%, indicating that the positive electrode sheet using hafnium dioxide nanomaterials as the matrix layer can effectively improve the performance stability of sodium telluride batteries, effectively curb the shuttle effect, and effectively improve the battery life. The conductivity of Example 1 is 0.316S / m, and the conductivity of Comparative Example 1 is 0.06S / m, indicating that the larger porosity and larger specific surface area can provide channels and interfaces for the diffusion and migration of sodium ions and multi-tellurides, solving the safety problems caused by ohmic polarization. Figure 5 This is the SEM electron microscope image of Te / graphene of Comparative Example 1. It can be seen that it is difficult for graphene to form a stable interconnected three-dimensional structure. The graphene nanosheets are randomly stacked with tellurium nanoparticles and do not have good dispersion.

[0112] Compared with Example 1, Comparative Example 2 uses a larger nanosheet size design, and the diameter of the hafnium dioxide nanosheet ranges from 400 to 500 nm. For hafnium dioxide nanosheets with a larger sheet diameter, as expected, increasing its sheet diameter can expand the porosity of the matrix layer and increase the loading capacity of elemental tellurium, thereby expected to increase the capacity of the battery. However, the conductivity of this nanosheet is not ideal and needs to be improved by compaction treatment. Because the sheet diameter of the hafnium dioxide nanosheet is too large, after the elemental tellurium loading and compaction treatment, the pores become smaller than expected, resulting in a smaller loading amount of elemental tellurium than expected. The effect of the sheet diameter of the hafnium dioxide nanosheet on its porosity and elemental tellurium loading is a complex issue: within an appropriate range, an increase in the sheet diameter will increase the surface area and pore structure, which helps to increase the porosity and the loading amount of elemental tellurium. However, a sheet diameter that is too large may cause the nanosheets to be tightly packed, resulting in a smaller porosity than expected. In addition, compaction treatment will also affect the pore structure of the nanosheets and the loading capacity of tellurium.

[0113] Compared with Example 1, the thickness of the hafnium dioxide nanosheets in Comparative Example 3 is 10 to 15 nm. By increasing the thickness of the nanosheets, the conductivity of the matrix layer material and the mechanical stability of the matrix layer can be effectively improved, which is expected to improve the cycle performance of the battery. However, if the thickness of the nanosheets is too large, the binding energy demand between the materials will increase, so a higher compaction density is required. At high compaction density, the volume occupied by the nanosheets in the pores of the matrix layer will increase, resulting in a significant decrease in porosity. Therefore, after the loading and compaction treatment of elemental tellurium, the porosity is smaller than expected, resulting in a smaller loading amount of elemental tellurium than expected.

[0114] Compared with Example 1, Comparative Example 4 uses a melting method to load tellurium. As expected, using a melting method to load tellurium on a matrix layer material composed of hafnium dioxide nanosheets can form a good bond between the tellurium and the hafnium dioxide nanosheets and the matrix layer, as well as a higher tellurium loading amount. However, as can be seen from Table 1, the use of a melting method to load tellurium abnormally results in a decrease in tellurium loading amount and poor cycle performance due to the weak binding energy between the hafnium dioxide nanosheets and the matrix layer. This is because at higher temperatures, the binding energy of liquid tellurium on the surface of the matrix layer material composed of hafnium dioxide nanosheets with smaller sheet diameters is too high, resulting in excessive viscosity, making it impossible to form a uniform wetting layer between the hafnium dioxide nanosheets and the matrix layer, ultimately resulting in a tellurium loading amount far lower than expected. Therefore, Example 1 selected the potassium hydroxide dissolution sedimentation method. The method has good tellurium elemental wettability and uniform loading, and by regulating the functional groups of the surface layers of hafnium dioxide and aluminum foil, a transition from oxygen terminal to hydroxyl terminal is achieved, thereby improving the binding force between hafnium dioxide nanosheets and between aluminum foil and the matrix layer of hafnium dioxide nanomaterial. Through this method, Example 1 can not only achieve uniform infiltration when loading tellurium element, but also enhance the binding force between hafnium dioxide nanosheets and between aluminum foil and the matrix layer of hafnium dioxide nanomaterial.

[0115] Compared with Example 1, the compaction density in Comparative Example 5 is smaller. It is foreseeable that the use of a smaller compaction density can maintain the porosity of the positive electrode sheet at a higher level, and obtain a good porosity, ultimately achieving a higher tellurium loading and a higher battery capacity. However, the test results show that for a battery with a low compaction density, although the porosity of its positive electrode sheet and the specific surface area of ​​the compacted hafnium dioxide nanomaterial matrix layer are slightly higher than those in Example 1, the mass surface density of the tellurium element and the battery capacity are close to those in Example 1, but the attenuation ratio per cycle is large, the conductivity decreases, and the battery capacity is far below the expected level. This shows that the compaction density is too small, which increases the spacing between the hafnium dioxide nanosheets, resulting in a decrease in the bonding force between the hafnium dioxide nanosheets. In addition, since tellurium element is a poor conductor, its mass surface density should meet the physical limitations in the hafnium dioxide nanomaterial matrix layer, and too low a compaction density may cause uneven distribution of tellurium element, thereby affecting the overall conductivity. Therefore, in order to improve these problems, it is necessary to properly adjust the compaction density to meet the bonding requirements between the hafnium dioxide nanosheets. At the same time, it is necessary to ensure that the tellurium element is evenly distributed in the hafnium dioxide nanomaterial matrix layer to improve the conductivity and battery capacity.

[0116] Compared with Example 1, the compaction density in Comparative Example 6 is larger. It can be foreseen that the use of a larger compaction density can effectively increase the binding energy between the hafnium dioxide nanosheets and the aluminum foil and the hafnium dioxide nanomaterial matrix layer, and effectively increase the conductivity of the positive electrode sheet, thereby improving the safety performance of the battery. However, this solution also has serious problems. Although the mass surface density and conductivity of the tellurium element are slightly higher than those in Example 1, and the attenuation ratio per cycle is close to that in Example 1, the porosity of the positive electrode sheet is poor, the specific surface area of ​​the matrix layer after compaction is small, and the battery capacity is significantly reduced. This shows that the compaction density is too large. Although it effectively reduces the spacing between the hafnium dioxide nanosheets and increases the binding force between the hafnium dioxide nanosheets, the cycle performance is significantly improved, but the lower porosity is not conducive to the loading of active substances and the diffusion of carriers on the interface during operation, thereby affecting the battery capacity performance.

[0117] For the Te / HfO of Example 1 2 The Te / graphene of Example 1 was subjected to XRD and SEM analysis; the positive electrode porosity, the specific surface area of ​​the matrix layer after compaction, the mass surface density of the tellurium element, the positive electrode sheet per cycle decay ratio, the positive electrode sheet conductivity, and the battery capacity of Examples 1 to 4 and Comparative Examples 1 to 6 were tested; the sodium tellurium battery prepared in Example 1 was tested for cycle stability; and the sodium tellurium battery of Example 1 and Comparative Example 1 was tested for battery rate performance. The specific test methods are:

[0118] The XRD test method uses a Bruker D8 Advance tester. After the sample to be tested is fully ground, 30 mg of the powder sample is spread flat on a conductive tape for sample preparation; the test angle range is 10-80°, the step angle is 0.1°, the scanning speed is 5° / min, and the X-ray wavelength used is The sample is Te / HfO of Example 1 2 and Te / graphene of Comparative Example 1.

[0119] The SEM test method uses the instrument model Hitachi S-4800. After the sample to be tested is fully ground, the trace powder sample is flatly spread on the conductive tape for sample preparation. The acceleration voltage of the test is 20kV, the scanning rate is 10μm / s, the acquisition interval is 50ms, and the resolution is 5nm. The test samples are Te / HfO 2 , Te / graphene and Te / HfO after battery cycle test 2 .

[0120] The battery cycle performance test, battery capacity test, and battery rate performance test were performed using the LAND CT2001A battery tester. The assembled battery was connected to the device channel port, the fixed charge and discharge rate was set to 1.0C, the number of cycle test cycles was 100, the voltage window was set to 0.5-2.5V, and the coulomb efficiency was calculated according to the cyclic voltammetry test data. Coulomb efficiency = output power during discharge / input power during charging × 100%.

[0121] Calculation method for the attenuation ratio of each cycle of the positive electrode: First, record the initial capacity value of the positive electrode before the cycle test. This is usually the result of a charge and discharge test on the positive electrode before starting the cycle test. When performing the cycle test, record the capacity value of the positive electrode after each cycle. The cycle attenuation ratio can be calculated by the following formula: Cycle attenuation ratio = (initial capacity - final cycle capacity) / initial capacity × 100%, where the final cycle capacity refers to the capacity value of the positive electrode after the last cycle.

[0122] Battery capacity test: The charge and discharge rate of the test is 0.1C, and the battery capacity statistics are the discharge capacity of the second cycle.

[0123] Battery rate performance test: Use LAND CT2001A battery tester, set the rate change cycle to 10 cycles, the rate ranges are 0.1, 0.2, 0.5, 1.0, 2.0, 5.0, 10.0C, and the total number of test cycles is 100.

[0124] Conductivity test: Place the sample to be tested on the sample table of the four-probe resistance tester. After adjusting the levelness of the sample, use the resistance test probe to test the flat area of ​​the sample to be tested. The test range is 200 milliohms to 20 ohms.

[0125] Porosity (or specific surface area) test: Dry and crush the sample, sieve to obtain a uniform particle size distribution, transfer the sample to the adsorption tube, connect the vacuum system to evacuate, treat it under high temperature conditions to remove impurities, and then make the sample reach a constant weight state. Connect the treated sample to the adsorption workstation, introduce a certain partial pressure of nitrogen into the sample pipeline under liquid nitrogen temperature (-196°C), record the nitrogen adsorption amount under equilibrium state, and obtain the adsorption isotherm of the sample to nitrogen molecules. Based on the nitrogen adsorption isotherm data, the BET model is used to calculate the specific surface area of ​​the sample. Heat the sample to normal temperature to desorb the adsorbed nitrogen, record the desorption amount and the final nitrogen residual amount, and calculate the micropore volume of the sample based on the density.

[0126] Measurement of mass surface density of tellurium element: Thermogravimetric analysis (TG) is a technique commonly used to measure the change of sample mass with temperature. The steps for measuring the mass surface density of tellurium element loaded on the electrode are as follows: prepare the tellurium element sample loaded on the electrode, and ensure that the mass and shape of the sample meet the test requirements; use a balance to accurately weigh the mass of the sample and record the mass value; set up the TG instrument according to the instructions of the operation manual; ensure that the selected temperature range and heating rate are suitable for the test sample; place the sample in the sample chamber of the TG instrument and ensure that the sample is in good contact with the instrument; start the TG instrument and start the temperature rise and fall cycle test; during the test, the instrument will heat up and record the data of the sample mass changing with temperature. By analyzing the data obtained from the test, a curve of the mass change of the sample with temperature can be obtained. Find the temperature range with the largest mass reduction from the curve, which corresponds to the weight loss process of tellurium element in the sample. According to the sample mass and the surface area of ​​the sample, the mass surface density of tellurium element can be calculated. The calculation formula of mass surface density is: mass surface density = mass / surface area.

Claims

1. A hafnium dioxide nanomaterial, characterized in that: The hafnium dioxide nanomaterial is composed of cross-connected hafnium dioxide nanosheets to form a cluster structure; the crystal structure of the hafnium dioxide nanosheet is an orthorhombic system, the shape of the hafnium dioxide nanosheet is round, the sheet diameter is 200-400nm, and the thickness is 5-10nm.

2. A method for preparing the hafnium dioxide nanomaterial as claimed in claim 1, characterized in that: The steps include: (I) Preparation of precursor: Hafnium telluride tetrahydrate is mixed with methyl thioglycolate, and after sufficient stirring, alkyl alcohol amide and ammonium fluoride are added to react. After the reaction is completed, the precipitate is collected by filtration and washed to obtain a precursor; (II) Low-pressure temperature-controlled oxidation: the precursor prepared in step (I) is subjected to a pre-oxidation heating treatment, followed by a deep oxidation heating treatment, followed by cooling to obtain amorphous hafnium dioxide; (III) vacuum freeze drying: the amorphous hafnium dioxide obtained in step (II) is mixed with ethylene glycol and subjected to vacuum pre-freezing treatment, followed by drying and heating to obtain amorphous hafnium dioxide nanospheres; (IV) Annealing and purification: The amorphous hafnium dioxide nanospheres prepared in step (III) are annealed to obtain hafnium dioxide nanomaterials.

3. The preparation method according to claim 2, characterized in that: In step (I), the mass ratio of hafnium telluride tetrahydrate, methyl thioglycolate, alkyl alcohol amide and ammonium fluoride is (3-4):(1-1.2):(0.8-1.0):(0.2-0.3).

4. The preparation method according to claim 2, characterized in that: In step (IV), the annealing treatment is carried out at a temperature of 200 to 220° C. and for a time of 3 to 4 hours.

5. A positive electrode sheet, comprising a positive electrode current collector, characterized in that: It also includes a matrix layer arranged on one side of the positive electrode current collector and an active substance loaded on the matrix layer; the positive electrode current collector is aluminum foil, the matrix layer is the hafnium dioxide nanomaterial according to claim 1, and the active substance is tellurium element.

6. The positive electrode sheet according to claim 5, characterized in that: The thickness of the matrix layer is 50-70 μm.

7. A method for preparing a positive electrode sheet according to any one of claims 5 to 6, characterized in that: The steps include: (1) Active material loading: tellurium powder and potassium hydroxide are mixed and ground evenly, sieved and then distilled water is added, stirred and dissolved to obtain a yellow mixed solution, then the yellow mixed solution is added dropwise to the powder of the hafnium dioxide nanomaterial according to claim 1 to form a light yellow slurry, anhydrous ethanol is added, and then the light yellow slurry is wet-milled and dried to obtain tellurium-loaded hafnium dioxide; (2) Pretreatment of the positive electrode current collector: the aluminum foil is flattened and then annealed. The treated aluminum foil is immersed in a mixed solution of iodine methanol and phosphoric acid. After standing, it is taken out, washed and dried at low temperature to obtain a pretreated aluminum foil; (3) Vacuum coating of positive electrode sheet: The aluminum foil pretreated in step (2) is placed in a vacuum coating machine, and the tellurium-loaded hafnium dioxide prepared in step (1) is coated on the surface of the aluminum foil under vacuum heating conditions and then compacted to obtain a positive electrode sheet.

8. The preparation method according to claim 7, characterized in that: In step (3), the compaction density of the positive electrode sheet is 3.5 to 4 g / cm 3 .

9. A sodium tellurium battery, characterized in that: The positive electrode sheet comprises the positive electrode sheet as described in any one of claims 5 to 6.

Citation Information

Patent Citations

  • Novel electrode material of sodium-ion battery and application of electrode material

    CN105185958A

  • Preparation method of platy hafnium oxide nano powder

    CN101844807A

  • Application of tellurium based material serving as negative electrode active material in sodium-based dual-ion cell, sodium-tellurium dual-ion cell and preparation method thereof

    CN108321387A